A Season of Opera : From Orpheus to Ariadne - Lee, M. Owen, 1930-2019 (Book collections on Project MUSE., 1998)
"Father Owen Lee is internationally known for his intermission commentaries featured during the Saturday afternoon broadcasts from the Metropolitan Opera House in New York. A Season of Opera: From Orpheus to Ariadne gathers together for the first time Father Lee's best broadcast and cassette commentaries, public lectures, and articles on twenty-three works for the musical stage. The essays range from the pioneering Orpheus of Monteverdi to the forward-looking Ariadne of Richard Strauss." "Opera lovers, or anyone interested in psychology and mythology, humanities and comparative literature, or the art of the essay will welcome this book."--Jacket.